Penerapan Sanksi Terhadap Pelaku Ujaran Kebencian di Pengadilan Negeri Pekanbaru - Fahmi; Rai Iqsandri; Rizana (Jurnal Hukum Respublica, 2020)
The problems examined in this study are how to apply the sanctions against the perpetrators of hate speech in the Pekanbaru District Court and what are the obstacles faced in applying the sanctions against the perpetrators of hate speech in the Pekanbaru District Court. This research method is carried out directly in the field according to the type of sociological legal research. The results of the study show that the application of sanctions against hate speech offenders in the Pekanbaru District Court is not optimal. Factors that hinder the application of sanctions against hate speech offenders do not realize that what they are doing is a criminal act that has a fairly severe sanction in accordance with the law.